Adaptation and psychometric study of the scale for the measurement of fear and anxiety of COVID-19 disease in pregnant women (AMICO_Pregnant) - Muñoz-Vela, Francisco Javier; Rodríguez-Díaz, Luciano; Fernández-Carrasco, Francisco Javier; Allande-Cussó, Regina; Vázquez-Lara, Juana Maria; Fagundo-Rivera, Javier; Gómez-Salgado, Juan (Frontiers in Public Health, 2023)
Objective: The aim of this research was to adapt and explore the psychometric properties of a specific scale to assess the levels of fear and anxiety of COVID-19 disease in pregnant women. Methods: An adaptation phase, by a panel of experts, and a psychometric descriptive cross-sectional study were carried out on the final version of the 16-item, self-administered AMICO_Pregnant scale. Univariate and bivariate analyses were carried out, followed by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The consistency of the scale was assessed using the Omega coefficient and Cronbach's Alpha. Results: With a sample of 1013 pregnant women living in Spain and over 18 years of age, the mean age was 33 years. The scale showed a bifactor structure (anxiety and fear) that was confirmed with good fit parameters. Reliability was assessed in terms of internal consistency by calculating Cronbach's Alpha coefficient (0.95) and McDonald's Omega coefficient (0.94) as indicators of robustness of the scale's reliability. Conclusion: The AMICO_Pregnant scale of 16 items with scores ranging from 1 to 10 is a valid and reliable tool to assess levels of anxiety and fear of COVID_19 in Spanish pregnant women. Pregnant women have shown moderate levels of anxiety and fear regarding the COVID_19 disease in the final phase of the pandemic.